Application of the Weighted Sum Model Method in Determining the Location of Family Planning Counseling at the North Sumatera BKKBN - Lubis, Zahwa Putri; Sary, Yoshida (Tsabit Journal of Computer Science, 2024)
To determine the location of Family Planning Counseling automatically, this research developed a web-based decision support system using the Weighted Sum Model (WSM) method with PHP programming and a MySql database. This system uses several variables as decision support indicators such as the number of couples of childbearing age, number of contraceptive users, location accessibility, costs, number of family cards, number of family planning participants, number of children and education, with 33 alternative regencies/cities in Sumatera Utara region. Based on the analysis carried out, the results of the top 5 alternatives are regencies/cities, namely Deli Serdang (127851), Medan (103020), Langkat (67047), Simalungun (53025), and Asahan (48598). So it can be concluded that this research achieved the results expected by the BKKBN.